European Society of Cardiology Heart Failure Long‐Term Registry (ESC‐HF‐LT): 1‐year follow‐up outcomes and differences across regions. (20th June 2016) - Crespo‐Leiro, Maria G.; Anker, Stefan D.; Maggioni, Aldo P.; Coats, Andrew J.; Filippatos, Gerasimos; Ruschitzka, Frank; Ferrari, Roberto; Piepoli, Massimo Francesco; Delgado Jimenez, Juan F.; Metra, Marco; Fonseca, Candida; Hradec, Jaromir; et al.
Abstract: Aims: The European Society of Cardiology Heart Failure Long‐Term Registry (ESC‐HF‐LT‐R) was set up with the aim of describing the clinical epidemiology and the 1‐year outcomes of patients with heart failure (HF) with the added intention of comparing differences between participating countries. Methods and results: The ESC‐HF‐LT‐R is a prospective, observational registry contributed to by 211 cardiology centres in 21 European and/or Mediterranean countries, all being member countries of the ESC. Between May 2011 and April 2013 it collected data on 12 440 patients, 40.5% of them hospitalized with acute HF (AHF) and 59.5% outpatients with chronic HF (CHF). The all‐cause 1‐year mortality rate was 23.6% for AHF and 6.4% for CHF. The combined endpoint of mortality or HF hospitalization within 1 year had a rate of 36% for AHF and 14.5% for CHF. All‐cause mortality rates in the different regions ranged from 21.6% to 36.5% in patients with AHF, and from 6.9% to 15.6% in those with CHF. These differences in mortality between regions are thought reflect differences in the characteristics and/or management of these patients. Conclusion: The ESC‐HF‐LT‐R shows that 1‐year all‐cause mortality of patients with AHF is still high while the mortality of CHF is lower. This registry provides the opportunity to evaluate the management and outcomes of patients with HF and identify areas for improvement.